Elasticities of regional and local administrations expenditures : the portuguese case - Mourão, Paulo (2005)
This work analyses the evolution of real public expenditures of local and regional administrations (LRA), in Portugsl, in the period after the Second World War. It also aims to estimate the elasticities associated to determinants, which explain the found growth. As most relevant results, it is focused that real public espenditures of LRA did not increase in a constant way - the most significant period of growth was between 1974 and 1990. A long-term relation was found among real public expenditures of LRA ( as a proportion of real Gross National Product), the Number of Employees in Public Administration, the Number of Unemployed and Public Revenues. These results are consistent with the bureaucracy being a source of discouragement referring to the decentralized public expenditures.